南極沿岸・陸上生態系モニタリング計画の新展開 - 伊村, 智; Satoshi, Imura (2013)
The Antarctic Nearshore and Terrestrial Observing System (ANTOS) is an international initiative focused at coordinating and expanding the efforts of all nations and programs that gather data from nearshore and terrestrial ecosystems. The specific aim of ANTOS is to develop a coherent and efficient observing system that will deliver the observations required to identify current and future impacts of global and local change. The objectives of the program are; 1) Design and implement a comprehensive and multidisciplinary observing system for Antarctic near-shore and terrestrial ecosystems, 2) Advocate and guide the development of new observation technologies, 3) Integrate and coordinate national and international projects and unify and harmonise current observation efforts, and 4) Facilitate and develop data sharing. ANTOS and SOOS (Southern Ocean Observing System) will work as a battery of monitoring program on Antarctic environment. Many areas such as the moss beds at Casey and the LTER program in the Dry Valleys have long term observing systems in place. ANTOS aims to link and harmonise such activities into a co-ordinated program to maximise effort, investment and outcomes, provide a platform for the new SCAR programs and provide information for use by the CEP and COMNAP. This plan is discussed to be the next Expert group in SCAR. 第4回極域科学シンポジウム 特別セッション：[S] 南極研究の将来展望―第Ⅸ期6か年計画策定に向けて 11月14日（木） 国立極地研究所 ２階大会議室 conference object